1932
DOI: 10.1042/bj0260403
|View full text |Cite
|
Sign up to set email alerts
|

Wax metabolism in the leaves of Brussels sprout

Abstract: IN connection with an investigation which is being made in this laboratory into the metabolism of paraffins in the higher plants it was thought that further light might be thrown on the chemistry of paraffin synthesis in the leaf if the composition of a leaf-wax known to contain large amounts of paraffin could be determined at various stages throughout the life history of the leaf. The wax of cabbage leaves (Brassica oleracea v. capitata), which was shown by Channon and Chibnall [1929] to consist chiefly of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1943
1943
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…However, in the most mature leaves the degree of unsatura- tiona rapidly decreased in S. halepense and increased rapidly in P. dactylifera. The increase with age of unsaturation of the fatty constituents is in agreement with previous work (8,13), but the significance of the rapid decrease of the iodine number with age of S. halepense is not known. It may be that as the old plant parts become desiccated, the unsaturated lipid compounds of this species are oxidized more rapidly by atmospheric oxygen.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, in the most mature leaves the degree of unsatura- tiona rapidly decreased in S. halepense and increased rapidly in P. dactylifera. The increase with age of unsaturation of the fatty constituents is in agreement with previous work (8,13), but the significance of the rapid decrease of the iodine number with age of S. halepense is not known. It may be that as the old plant parts become desiccated, the unsaturated lipid compounds of this species are oxidized more rapidly by atmospheric oxygen.…”
Section: Introductionsupporting
confidence: 81%
“…According to earlier studies on Brussels sprout (13) and the runner bean (8), wax is steadily synthesized as the plant matures and is not catabolized. If this behavior is considered general, then the decrease with age of wax yield in several cases of the present study was only an apparent decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Wax components applied to leaf surfaces undergo metabolic interconversions (Kolattukudy and Liu, 1970;Cassagne and Lessire, 1975). From measurements of the amount of wax present on brussels sprout and bean plants during their growth period, Chibnall and co-workers concluded that weathering was probably the only significant reason for loss of cuticular waxes (Sahai and Chibnall, 1932;Jordan and Chibnall, 1933;Chibnall and Piper, 1934), and to date little evidence to the contrary is avail able. From measurements of the amount of wax present on brussels sprout and bean plants during their growth period, Chibnall and co-workers concluded that weathering was probably the only significant reason for loss of cuticular waxes (Sahai and Chibnall, 1932;Jordan and Chibnall, 1933;Chibnall and Piper, 1934), and to date little evidence to the contrary is avail able.…”
Section: A Degradation Of Waxesmentioning
confidence: 99%
“…Epicuticular wax (ECW) 4 formation is a continual process on all plant organs except roots (8,17). Air temperature, moisture stress, radiant energy, relative humidity, air pollutants, plant age, and certain soil-applied pesticides are factors that affect the quantity and quality of ECW deposition (2,5,10,19,20,23).…”
Section: Introductionmentioning
confidence: 99%